OP05 Crohn's disease exclusion diet is equally effective but better tolerated than exclusive enteral nutrition for induction of remission in mild-to-moderate active paediatric Crohn's disease: a prospective randomised controlled trial. (25th January 2019) - Van Limbergen, J; Wine, E; Assa, A; Sigall Boneh, R; Shaoul, R; Kori, M; Cohen, S; Peleg, S; Shamaly, H; On, A; Milman, P; Abramas, L; et al.
Abstract: Background: Exclusive enteral nutrition (EEN; consumption of a liquid formula without other food for 6–8 weeks) is the recommended first-line therapy for induction of remission in children with mild-to-moderate Crohn's disease (CD). The CD exclusion diet (CDED) is a whole food diet coupled with partial enteral nutrition (PEN), designed to reduce exposure to dietary components hypothesised to negatively affect the microbiome, intestinal barrier, and innate immunity. Methods: The CDED study was a 12-week prospective, international, multi-centre RCT in children with mild-to-moderate luminal CD <3 years comparing CDED to EEN. Children aged 6–18 years with a paediatric CD activity index (PCDAI) ≥10, + elevated inflammatory markers, were randomised to one of the two groups: Group 1, CDED Stage 1 diet + 50% calories from PEN (Modulen, Nestle) for 6 weeks, followed by CDED Stage 2 + 25% PEN for the next 6 weeks; Group 2 EEN for 6 weeks (Modulen) followed by 6 weeks of free diet with 25% supplemental calories from PEN. The primary endpoint was tolerance to diet, measured by withdrawals for refusal to continue diet and poor adherence (measured by a modified MARS questionnaire and physician's assessment). Secondary endpoints included Week 6 intention to treat (ITT) remission defined by PCDAI ≤10 but also with the more stringent definition (PCDAI < 10), and corticosteroid (CS) free ITT sustained remission Week 12. Results: Seventy-eight patients meeting inclusion exclusion criteria were randomised to CDED+PEN (40)or to EEN (38), four withdrew because of intolerance to diet by 48 h (all EEN). Seventy-four remaining patients (mean age 14.2 ± 2.7 years) were included in the remission analysis. Median PCDAI at baseline was 25 (IQR 20–35) for CDED and 27.5 (IQR 18.75–32.5) in EEN; p = 0.89. Tolerance was present in 39/40 (97.5%) CDED and in 28/38(73.7%) EEN ( p = 0.003). Poor compliance was similar [7/40 (17.5%) vs. 8/34 (23.5%); p = 0.52]. Week 6 ITT CS-free remission PCDAI ≤10 occurred in 32/40 (80%) in CDED vs. 25/34 (73.5%) with EEN ( p = 0.51). Using the more stringent PCDAI < 10, remission was 30/40(75%) CDED and 20/34 (59%) EEN p = 0.38. Median CRP decreased from Week 0 to 6 in both groups (23.6 to 5 g/l with CDED; p < 0.001; 24 to 4 g/l with EEN; p < 0.001). Sustained CS free remission at Week 12 PCDAI ≤10 was 28/40 (70%) with CDED+PEN and 14/34 (41.2%), in the EEN followed by PEN +free diet p = 0.01. Conclusions: Both diets result in high rates of ITT CS free remission with a significant decrease in inflammation. CDED with PEN has superior tolerance and sustained remission by Week 12. These data support the use of CDED+PEN as a first-line therapy for children with luminal mild-to-moderate active CD. They also support the concept that diet plays a role in inflammation in CD